Yearbook for European Jewish Literature Studies : Jahrbuch für europäisch-jüdische Literaturstudien (De Gruyter, 2014)
The Yearbook of the Association for European-Jewish Literature Studies constitutes an interdisciplinary forum for the research of Jewish writing in all its diversity and complexity. Each issue addresses a different thematic topic from a variety of perspectives. The yearbook underlines the transnational dimension of Jewish writing and stresses the relevance of literature for an exploration of Jewish existence in Europe.